An assessment of the taxonomic validity of three species of marsupial frogs (Anura: Hemiphractidae: Gastrotheca) from the Yungas of Bolivia based on external morphology and cranial osteology - Lansac, Claudia; Aguayo, Rodrigo; de La Riva, Ignacio (Zootaxa, 2021)
The genus Gastrotheca (Anura: Hemiphractidae) is a group of marsupial frogs particularly diverse in Andean regions. Several taxonomic studies of this genus have been conducted in the humid cloud forests—or Yungas—of the Andean eastern slopes of central Bolivia (departments of Cochabamba and Santa Cruz). Yet, the distinction among three species that occur sympatrically in these forests, G. lauzuricae (proposed as a junior synonym of G. coeruleomaculatus in 2015), G. piperata, and G. splendens, remains unclear since the morphological characters that purportedly support their differentiation are variable and partly shared among them. We have carried out external morphological studies, including multivariate morphometric analyses, to assess how they support the taxonomic status of these three species. We also evaluated characters of the cranial osteology of a sample of six individuals using micro CT-scanning. Principal component and linear discriminant analyses resulted in a great overlap among the putative species. Cranial osteological comparisons did not reveal highly significant differences among them, but suggested that different degrees of hyperossification could be related to the developmental state of individuals. Our results indicate that most morphological and osteological reported differences between the three species likely represent intraspecific variation. Thus, we propose that the three nominal species belong to a single biological entity, for which the name Gastrotheca splendens (Schmidt, 1857) has priority. We also restrict the name Gastrotheca coeruleomaculatus (Werner, 1899) to externally similar congeneric populations from the Yungas forests of department of La Paz, but highlighting the need of a detailed evaluation of their taxonomic identity.